2021
DOI: 10.1111/hsc.13409
|View full text |Cite
|
Sign up to set email alerts
|

Safety and danger: Perceptions of the implementation of harm reduction programs in two communities in Nova Scotia, Canada

Abstract: People who use substances (PWUS), and specifically individuals who use injection drugs and/or smoke crack cocaine, experience risks which harm reduction programmes can help reduce. Prior to implementing harm reduction programmes, however, it is critical to understand how programme users and others in the community perceive the programmes as their perceptions may influence implementation.A mixed-methods study asked PWUS and key informants about their perceptions of implementing five harm reduction programmes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In a study by Jackson et al, (2022), PWUD in Nova Scotia primarily believed a SCS should be located in the same place as their local needle exchange, indicating the importance of a centralized and easily accessible location [ 30 ]. Many participants also suggested that SCS should be mobile, which can also increase accessibility [ 30 ]. However, finding a suitable location that community members can agree on can also be a contentious issue, which may be particularly relevant for smaller more tight-knit communities, as was the case for The Spot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Jackson et al, (2022), PWUD in Nova Scotia primarily believed a SCS should be located in the same place as their local needle exchange, indicating the importance of a centralized and easily accessible location [ 30 ]. Many participants also suggested that SCS should be mobile, which can also increase accessibility [ 30 ]. However, finding a suitable location that community members can agree on can also be a contentious issue, which may be particularly relevant for smaller more tight-knit communities, as was the case for The Spot.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, having the site integrated within other existing services as a one-stop-shop for PWUD within Sudbury could facilitate connections and referrals to other services. In a study by Jackson et al, (2022), PWUD in Nova Scotia primarily believed a SCS should be located in the same place as their local needle exchange, indicating the importance of a centralized and easily accessible location [30]. Many participants also suggested that SCS should be mobile, which can also increase accessibility [30].…”
Section: Discussionmentioning
confidence: 99%
“…The role of harm reduction services within communities have long reflected a central tension: in contrast with abstinence and criminalization models, harm reduction is often socially and politically criticized as enabling drug use and making neighborhoods less safe [67][68][69], while research consistently finds harm reduction to yield positive outcomes for both service users and surrounding communities [70,71]. In addition to improving the health and wellbeing of people using drugs, evidence suggests that those accessing harm reduction services are more likely to ultimately seek treatment and pursue recovery [49,70,72,73].…”
Section: The Tension At the Center Of Harm Reduction Policymentioning
confidence: 99%
“…At the same time, certain people are constructed as “vulnerable” through policy discourse (Larios and Paterson 2021). In public health and policy literatures, opposition to health programming, in the community and in carceral institutions, is linked to the association of programs with danger, particularly that presented by criminalized populations, and the desire for those populations to be spatially contained to protect those deemed vulnerable (Jackson et al 2021). Literature on dangerous offenders and protective surveillance has long recognized mobilization against those labelled “risky” (Matravers and Hughes 2003; Shore 2021).…”
Section: Literaturementioning
confidence: 99%